Study on the Group Investigation Toward Teacher to Reduce Student’s Anxiety in Speaking Skill - Wahyudi, Mohammad Arief; Azmi, Iis Ulul (Journal of English Teaching and Learning Issues, 2021)
This study aims to describe the study on the GI (Group Investigation) toward teacher to reduce students’ anxiety in speaking skill. The research design of the study was qualitative which focus on descriptive qualitative research. It involved the Vocational school students as the participants. The data were obtained through the observation during the teaching and learning process and an interview with the teachers. In this study, the researcher accomplished several steps to analyze the data, namely reducing data, presenting data, and drawing conclusion. The first research finding revealed that Group Investigation was used by the teacher and the students in the class and out of the class. The teacher utilized Group Investigation to reduce students’ anxiety in speaking skill toward teachers’ response. Meanwhile, the students used Group Investigation model to give corrections and suggestions on their friends’ speaking in pairs or groups. The second findings revealed that the students gave positive responses toward the use of Group Investigation on speaking. The students said that Group Investigation is a practical model, develop students’ speaking skill, and interesting medium which make student enthusiastic. It also developed the students speaking ability, and able to motivated the students in speaking.